Spotlight on necitumumab in the treatment of non-small-cell lung carcinoma - Thakur MK (Dove Medical Press, 2017)
Manish K Thakur, Antoinette J Wozniak, Department of Oncology, Karmanos Cancer Center, Detroit, MI, USA Abstract: The treatment options for metastatic non-small-cell lung cancer (NSCLC) have expanded dramatically in the last 10 years with the discovery of newer drugs and targeted therapy. Epidermal growth factor receptor (EGFR), when aberrantly activated, promotes cell growth and contributes in various ways to the malignant process. EGFR has become an important therapeutic target in a variety of malignancies. Small-molecule tyrosine kinase inhibitors (TKIs) of EGFR are being used to treat advanced NSCLC and are particularly effective in the presence of EGFR mutations. Monoclonal antibodies have also been developed that block the EGFR at the cell surface and work in conjunction with chemotherapy. Necitumumab is a second-generation fully human IgG1 monoclonal antibody that has shown promise in metastatic NSCLC. The benefit has mostly been restricted to squamous cell lung cancer in the frontline setting. Considering that the survival advantage for these patients was modest, there is a need to discover biomarkers that will predict which patients will likely have the best outcomes. This review focuses on the development and clinical trial experience with necitumumab in NSCLC. Keywords: lung cancer, squamous cell, necitumumab, EGFR